Determination of the active form of the tetranuclear copper sulfur cluster in nitrous oxide reductase - Johnston, Esther M. (2022)
This research was supported by NIH grant DK-31450 (E.I.S.) and National funds by FCT (Fundacao para a Ciencia e a Tecnologia) under the projects PEst-C/EQB/LA0006/2013 and PTDC/QUI-BIQ/116481/2010 (I.M.).